Aromatherapy and guided imagery non-pharmacological strategies for the management of late postoperative acute pain (Boletín Semillero de Investigación en Familia, 2024)
Introduction. There are different non-pharmacological strategies for its management, one of them is aromatherapy and guided images. This article aims to describe a nursing practice experience where these strategies were used to reduce the level of late pain in adults undergoing a surgical procedure. Materials and methods. It consisted of a practical project in which an intervention obtained from a systematic search of the scientific literature was applied. The NOC “Pain Level” was used before and after the intervention to evaluate: referred pain, facial expressions of pain, moans and screams, and restlessness. Results. The pain level decreased by 17.2%, going from 80% to 62.8%. The initial “Pain Level” of the NOC in the participants was: 50% substantial pain, 23% moderate pain, 15.3% severe pain, and 11.5% mild pain. The final NOC was 42.3% moderate pain, 30.7% mild pain, and 3.8% substantial pain. Furthermore, 23% of the patients reported not feeling any pain after the intervention. Regarding facial expressions of pain before the intervention, 76.9% of patients had moderate facial expressions, 3.8% had severe facial expressions, and 19.2% had none. After the intervention, moderate facial expressions were observed in 19.2% of patients, severe facial expressions in 3.8% and none in 76.9%. Conclusions. Previous experience motivates permanent evaluation with critical reading, in search of the best scientific evidence that supports nursing care, thus, the initial level of pain decreased compared to the post-intervention level, which was mostly located at a level " not proven.” level, suggesting that it is an effective intervention in the management of postoperative pain as indicated in the scientific literature.
Keywords: Imagery, Psychotherapy; Aromatherapy; Pain Management; Nursing; Pain, Postoperative.